2021
DOI: 10.1097/md.0000000000028406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 pandemic impact on the presenting complaints of the emergency department visits

Abstract: The impact of coronavirus disease 2019 (COVID-19) on economic and medical systems is significant, especially in the emergency department (ED). The patterns of ED visits have also changed significantly and may play a crucial role in rearranging medical resources to the most needed departments during the pandemic. This was a retrospective study conducted in hospitals of the Cathay Health System. All patients presented to the EDs between January 21, 2020 to April 30, 2020 (pandemic stage) and January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Numerous studies have demonstrated a significant decrease in ED visits across almost all age groups during the early phase of the pandemic [4,5,10,11]. However, contrary to the increased proportion of adults visiting the ED, from 60.5% (pre-pandemic) to 65.2% (pandemic) [11], our research revealed a decreased proportion and number of pediatric ED visits across all Cathay Health System hospitals during the pandemic season. Several factors, such as school closures, social distancing policies, and media influence, could have contributed to the decline in total pediatric ED visits [7,8].…”
Section: Discussioncontrasting
confidence: 73%
“…Numerous studies have demonstrated a significant decrease in ED visits across almost all age groups during the early phase of the pandemic [4,5,10,11]. However, contrary to the increased proportion of adults visiting the ED, from 60.5% (pre-pandemic) to 65.2% (pandemic) [11], our research revealed a decreased proportion and number of pediatric ED visits across all Cathay Health System hospitals during the pandemic season. Several factors, such as school closures, social distancing policies, and media influence, could have contributed to the decline in total pediatric ED visits [7,8].…”
Section: Discussioncontrasting
confidence: 73%
“…Our ED patient volume during the COVID-19 pandemic decreased from 52,369 to 35,561, in line with previous studies. [18,[21][22][23][24] However, during the same period, the number of patients hospitalized to the general ward for pneumonia through the ED increased from 248 to 306, and the number of patients admitted to the ICU increased from 73 to 154. We attributed this change to the avoidance of patients with fever, respiratory symptoms, or dyspnea in small and medium-sized hospitals, where securing IRs is difficult, and to the concentration of these patients in tertiary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted in Northern Taiwan revealed a 15.1% reduction in the total ED visits during the pandemic in 2020. 2 Our previous studies also revealed that nonemergency diagnoses (eg, congestive heart failure and constipation) were more affected by the pandemic than emergency diagnoses (eg, myocardial infarction and gastrointestinal bleeding). 3,4 Although the reasons for this may be complex, the fear of being infected is a possible explanation.…”
Section: Introductionmentioning
confidence: 86%